2021
DOI: 10.1002/admt.202100156
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Transparent Paper Based on PDMS–CNC Composite for Direct Printing

Abstract: Stretchable devices significantly expand the scope of applications such as flexible displays and wearable devices/sensors. To enable stretchable wearable electronics, methods for connecting unit devices and developing circuits are required. Previously, research was performed to manufacture circuits with 3D structures or patterns that remain intact when the flexible and stretchable substrates are deformed. A method for drawing a circuit directly on a substrate with a conductive ink pen is proposed, although it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The proposed stretchable and transparent device proved to be an appropriate substrate for resistor, inductor, and capacitor assemblies, preserving the transmittance of ≈70%. [ 388 ] In the particular case of inductors, fully 3D printed broadband conical‐shape structures (without resonant broadband features) were prepared by using engineered magnetic inks composed of 70 vol% of NEA121 polymer, and 30 vol% of iron‐cobalt. Three types of inductors were evaluated: i) an aerosol‐jet printed polymer core to be used as reference; ii) an iron‐cobalt core, and; iii) an iron‐based powder, the last 2 fabricated by paste‐extrusion.…”
Section: Printed Device Applicationsmentioning
confidence: 99%
“…The proposed stretchable and transparent device proved to be an appropriate substrate for resistor, inductor, and capacitor assemblies, preserving the transmittance of ≈70%. [ 388 ] In the particular case of inductors, fully 3D printed broadband conical‐shape structures (without resonant broadband features) were prepared by using engineered magnetic inks composed of 70 vol% of NEA121 polymer, and 30 vol% of iron‐cobalt. Three types of inductors were evaluated: i) an aerosol‐jet printed polymer core to be used as reference; ii) an iron‐cobalt core, and; iii) an iron‐based powder, the last 2 fabricated by paste‐extrusion.…”
Section: Printed Device Applicationsmentioning
confidence: 99%
“…Ryu et al reported a polydimethylsiloxane-cellulose nanocrystals composite paper that is highly flexible and stretchable while maintaining a high transmittance. [82] Their composite paper has a transmittance of ≈70% and can withstand over 800% tensile strain. The patterned circuits have only a minor increase in resistance after a 50% deformation and recovery.…”
Section: Chirality In Concentrated Cnc Liquid Crystal Suspensionsmentioning
confidence: 99%
“…Titanium (Ti) mesh is a typical metallic cranioplasty material for its excellent biocompatibility, high strength and perfect structural stability [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Meanwhile, PDMS is a soft material with high transmittance, biocompatibility, and penetrability [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. In this paper, we demonstrate a multifunctional cranial window device made from Ti and PDMS by a novel process.…”
Section: Introductionmentioning
confidence: 99%